Nanotechnology-Enabled Paradigms in Food Safety and Quality Assurance: A Comprehensive Review of Advanced Sensing, Packaging, And Processing Technologies - Simone Kaur (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2026)
The integration of nanotechnology into the food industry represents a transformative shift in how food safety, quality, and processing efficiency are managed. This article provides a critical examination of the current advancements in nanocomposite-based optical fiber sensors, nanobiosensors for adulterant detection, and the role of nanotechnology in food packaging and processing. As food security remains a global priority, the transition from conventional methods to sophisticated, real-time monitoring systems is essential. This research explores the theoretical underpinnings of carbon nanomaterials, protein nanotubes, and quantum dots, evaluating their efficacy in detecting contaminants and monitoring spoilage. Furthermore, the discussion extends to the socio-economic and technical implications of "Agri-food 4.0," where smart, sustainable, and sensing technologies converge. While the benefits of these materials are vast, the article highlights the necessity of addressing challenges related to toxicity, long-term stability, and the integration of non-targeted analytical methods for food fraud detection. By synthesizing recent literature, this review establishes a framework for future research, emphasizing the need for robust, cost-effective, and highly sensitive detection mechanisms that can be implemented at scale within the global food supply chain. The findings suggest that although nanotechnology currently offers unparalleled precision in food quality control, future adoption depends on overcoming regulatory hurdles and perfecting the interface between nanomaterial synthesis and sustainable industrial application.